If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = (y + -10) Reorder the terms: 6 = (-10 + y) Remove parenthesis around (-10 + y) 6 = -10 + y Solving 6 = -10 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 6 + -1y = -10 + y + -1y Combine like terms: y + -1y = 0 6 + -1y = -10 + 0 6 + -1y = -10 Add '-6' to each side of the equation. 6 + -6 + -1y = -10 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = -10 + -6 -1y = -10 + -6 Combine like terms: -10 + -6 = -16 -1y = -16 Divide each side by '-1'. y = 16 Simplifying y = 16
| 4/(-1) | | (3x-2/4)+(x+57/7)=13 | | x4/x=2 | | 30=90/x | | (9-2y)/3=y | | 6-6r-2=16 | | 30=90 | | 3(3*x+4*y+5)+2(2*x-4*y-3)= | | 3x-2/4+x+57/7=13 | | 1.8z-1(-2+z)=1.5 | | 25x^2y^4-121= | | 4(5x-3)=68 | | 2=(x-2.7)/0.6 | | 25=-8x-87 | | 6/7=2n | | 11z+35=100 | | 2(x+3)=x+5 | | 3x=35+(-2y) | | 12/17+3/17= | | -7x+37=-3(1+5x) | | 7(8-3x)=182 | | 0.19y+0.07(y+4000)=1060 | | 5x-14=4(2x+1) | | x-4/3+4/3=-x/5 | | 2-3x=62 | | 8x^2+28x=-24 | | 8y-6=2y+8 | | 26/57=849/5x | | 5x/6-(3-x)/8=4x+3/12 | | 2xsquared+12.5=0 | | 1=2-3v+2v | | 33=-8x-31 |